The time traveler's wife : a novel - Niffenegger, Audrey (MacAdam/Cage Pub., 2003)
Clare and Henry, deeply in love, try desperately to maintain normal lives even though he has been diagnosed with Chrono-Displacement Disorder, a condition in which his genetic clock periodically resets, pulling him through time to the past or future.